2014
DOI: 10.4103/0973-1482.137993
|View full text |Cite
|
Sign up to set email alerts
|

MRI diagnosis of intradural extramedullary tumors

Abstract: MRI is the preferred examination method for to diagnose IDEM tumors and provide a reliable imaging basis for clinical treatment and prognosis judgment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The reason for this is that previous studies have reported that the characteristics of spinal schwannoma and meningioma were cystic degeneration. 6,8,12,13 MRIs were performed using a spine coil with a GE Signa HDx 1.5T (GE Healthcare, Milwaukee, WI). We analyzed slice of the center of the tumor with fast spin echo T 2 weighted cross-sectional images (TR: 4,000-5,000ms, TE: 100ms, FOV: 120-140mm, matrix: 256 × 192, slice thickness/gap: 4-5 mm/0.5-1 mm) of a central tumor slice that was obtained prior to surgery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this is that previous studies have reported that the characteristics of spinal schwannoma and meningioma were cystic degeneration. 6,8,12,13 MRIs were performed using a spine coil with a GE Signa HDx 1.5T (GE Healthcare, Milwaukee, WI). We analyzed slice of the center of the tumor with fast spin echo T 2 weighted cross-sectional images (TR: 4,000-5,000ms, TE: 100ms, FOV: 120-140mm, matrix: 256 × 192, slice thickness/gap: 4-5 mm/0.5-1 mm) of a central tumor slice that was obtained prior to surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Takashima et al iso-or hyperintense: both are hypo-or isointense on T 1 -weighted images. 6,10,11 Thus, differences in the signal intensities (SIs) on T 2 weighted images may be useful to differentiate schwannomas from meningiomas. Prior studies 8,10 have attempted differentiation by visual assessment on T 2 weighted images, however, differentiation of these tumors remains difficult.…”
Section: Bjrmentioning
confidence: 99%
“…Meningioma signals are relatively homogenous; T1WI imaging has an equal or low signal, and T2WI imaging has a low or slightly high signal. Enhancement scanning of the meningioma reveals a heterogeneous enhancement, and the strengthening degree is lower than in neurogenic tumors 10) . In addition, the dural tail sign aids in the diagnosis of meningioma.…”
Section: Discussionmentioning
confidence: 85%
“…Meningioma is usually located in the cervical and upper thoracic segments, with the lumbosacral segment rarely involved. Most meningiomas have a longitudinal diameter <2.5cm, a transverse diameter <1.5cm, and no foraminal extension 10) . Meningioma signals are relatively homogenous; T1WI imaging has an equal or low signal, and T2WI imaging has a low or slightly high signal.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is the gold stan dard di ag nos tic tech nique for spi nal teratoma [1]. The tu mor pres ents as inhomogeneous in ten si ties in both T1-and T2-weighted im ages due to teratoma's tis sue heter o ge ne ity, which may con sist of solid and/or cys tic parts, fat, mucoid se cre tion or less com monly cal ci fi ca tion [10,[37][38][39][40]. Lipomatous tis sue and cal ci fi ca tion are of ten seen, the for mer pres ents hyperintense sig nal on T1 se quence and hypointense on T2 and fat sup pres sion, and the lat ter pres ents hypointense both on T1 and T2.…”
Section: Ra Dio Log I Cal Find Ingsmentioning
confidence: 99%